If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9w + -12w + -2 = 0 Reorder the terms: -2 + 9w + -12w = 0 Combine like terms: 9w + -12w = -3w -2 + -3w = 0 Solving -2 + -3w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3w = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3w = 0 + 2 -3w = 0 + 2 Combine like terms: 0 + 2 = 2 -3w = 2 Divide each side by '-3'. w = -0.6666666667 Simplifying w = -0.6666666667
| 3n+14=8 | | -x-92=-8x+62 | | -20k-16=-2(12k-19)-2k | | 0.6x+0.9=5.1 | | 8y+12=2-5y | | -4(1-12x)-5(12x-4)=-3x+4-7x | | -x-92=8x+62 | | 100=50+i | | 5e+2=20 | | 2g+20t+3= | | Y=25(15)+25 | | 2g+20t=3 | | -4(3y-1)=-16y | | x^3+6x-1=2x+4 | | y=400-55x | | 14+5y=50+4y | | 2x*4+3x*4=540 | | f(x)=4x^2+3x-10 | | 2c+13=5c-2-4c | | 1000(9x-10)=50(928+100x) | | -4x-84=61+x | | -52-3u=9 | | X-2(4-x)=31 | | 31+7(y-6)= | | 2x*2x=8x | | 3x^2+10+3=0 | | 7x+2+4x+1= | | -3d+8=-15-8d+5d | | -3x-45=11x+51 | | 42x^2-288x-39=0 | | 25-7p=19-6p | | P=r+s-1r |